Creating a blue economy: Research and innovation partnerships to accelerate the development of ocean-related industries - Fontes, M.; Sousa, C.; Conceição, O. (SPBPU IDE '19: Proceedings of the 2019 International SPBPU Scientific Conference on Innovations in Digital Economy, 2019)
The Blue Economy can be a driver of European growth, through the development of new competences and activities that enable a sustainable exploitation of ocean resources. This paper assesses the directions followed by the research and innovation activities performed by Portuguese organisations in the fields encompassed by the "Blue Economy", at the light of national and EU strategies. It analyses the projects developed by Portuguese actors in the context of European framework programmes to uncover: the areas privileged - namely the relative importance of emerging areas vs. new advances targeting established ones - and the relative position of different types of organisations in the developments taking place. The results point to stronger efforts in system domains related to marine resources and the marine environment and in some industry oriented domains. Among the latter, emerge new industries such as marine biotechnology and marine renewable energies and established industries exploiting marine living resources (fisheries, aquaculture). The results highlight the prominent position of research organisations in both new and established areas, as well as the relevant position of new technology intensive firms, in areas that require the development of application-oriented activities, where they often intermediate between research and industry. The results suggest that the international cooperation favoured by these projects permitted to open-up the national system, contributing to broaden the organisations' knowledge bases and to extend their international networks.